Instruments of State Regulation of Innovative Activity in the Russian Federation - Shichiyakh, Rustem A.; Tolkacheva, Svetlana V.; Shkiotov, Sergei V.; Karakaeva, Elena U.; Borlakova, Maryam I.; Zyablov, Andrey A. (International Journal of Economics and Financial Issues, 2016)
Innovative policy of the state - it is the socio-economic policy. It reflects the investment activity in the state, which reflects the direction, goals, forms of state authority in the field of science and technology. The financial growth of the state is based on a combination of extensive and intensive factors. Under extensive factors mean weight gain used in the production of resources under intensive factors - an increase in resources and performance properties of their use. In modern times, the ability to finance growth through involvement in the turnover of new resources are extremely limited. As a consequence become crucial intense moments. A decisive impact on the macro-economic characteristics have innovation. They affect the social strength, on the environment, on the intensity of international technical cooperation, the degree of public safety and the competitiveness of the national economy in the world economy. Currently, the innovation process determines the chances of becoming a state. Innovative activity is characterized by complexity and high risk. To initiate innovation is insufficient availability of internal incentives and capabilities. Here, a decisive driving force can be external stimuli and in particular state aid. Keywords: economic policy, innovation, government regulation JEL Classifications: O30, G28, K20